1988
DOI: 10.1063/1.454787
|View full text |Cite
|
Sign up to set email alerts
|

Broad-band structured fluorescence from NaI

Abstract: The emission spectrum of a molecular beam of NaI has been measured following excitation by the 248 nm KrF line of an excimer laser. The fluorescence structure, and the lifetime (17±2 ns), indicate the presence of a bound upper state not previously characterized. We identify this state as correlating with Na(3 2P)+I(5 2P3/2) atoms. Through numerical simulation using a Morse function representation for the upper state, we have determined approximate values for the well depth of 530±260 cm−1, well breadth of ∼1.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…58 Figure 7 offers a diagrammatic comparison of the potential energy curve for the fluorescing state determined by FTS with those for the C 0 + state derived from spectroscopic studies in the frequency domain. 33,58 The value of D e ′′′ ) 1863 cm -1 reported here quantitatively accounts for the splitting times obtained at different probe wavelengths as a function of photolysis energy.…”
Section: Fts-based Derivation Of E 2 (R) and E 3 (R)mentioning
confidence: 97%
See 2 more Smart Citations
“…58 Figure 7 offers a diagrammatic comparison of the potential energy curve for the fluorescing state determined by FTS with those for the C 0 + state derived from spectroscopic studies in the frequency domain. 33,58 The value of D e ′′′ ) 1863 cm -1 reported here quantitatively accounts for the splitting times obtained at different probe wavelengths as a function of photolysis energy.…”
Section: Fts-based Derivation Of E 2 (R) and E 3 (R)mentioning
confidence: 97%
“…The intense fluorescence monitored by these authors was attributed to bound f bound and bound f free transitions of NaI, which swamped the weak free f bound emission from the [Na‚‚‚1] ‡ * transition states of reaction 1 observed by the same group in separate experiments at shorter photolysis wavelengths. 33,56,57 Bluhm et al have subsequently established the depth of the potential minimum of a state labeled C 0 + leading to the same covalent asymptote by laser excitation spectroscopy across the wavelength range 239 e λ e 256 nm. 43,58 Prior to these two studies, the existence of a state with a shallow potential energy well in the same energy range had only been tentatively inferred from absorption cross section measurements 29 and discussed in relation to an early fluorescence quenching study.…”
Section: Fts-based Derivation Of E 2 (R) and E 3 (R)mentioning
confidence: 99%
See 1 more Smart Citation
“…Bluhm et al (5) and Bower et al (6) found a new bound state that leads to one of the Na(3p) asymptotes. Rose et al (7,8) performed femtosecond transition state spectra (FTS) measurements on the reaction of NaI, LiI, and NaBr.…”
Section: Introductionmentioning
confidence: 99%
“…The C(0 + ) state can be described by a shallow Morse potential having a dissociation energy between about 500 and 2000 cm -1 . ,, As the probe pulse prepares the C(0 + ) state near its dissociation limit, vibrational relaxation due to collisions with rare-gas atoms might stabilize the NaI molecules below the dissociation limit. Again, argon atoms should result in a larger momentum transfer than helium atoms.…”
Section: Resultsmentioning
confidence: 99%